Childhood: Biological fact of life and/or social and cultural construct - Nenadić Mile N. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
The author of the paper aligns himself with the new paradigm for investigating childhood which has appeared in recent years. The investigation starts off with the indications of early bodily foundation of a child's identity and goes on to emphasize that identity - the picture of oneself as the first fact of a child's relationship with life and world - has been built on new foundations, within social and cultural contexts. A contemporary human being constructs his or her identity, than leaves it behind, builds it again and the cycle repeats itself over the whole life span. The principle that identity is once acquired and kept forever has been abandoned. Identity hysterics has affected people of all ages, and children most of all. Childhood has become a structured reality of social life in which children's identities are shaped and changed. There is no natural identity which could be imposed forcibly and for a whole life. Identity changes in children and young people stem from the discrepancy between age as biological fact of life and age as cultural assumption. The author finds a model for age dependent identity shaping in the difference between gender and sex identities, as well as in other differences within categories resting on biological facts of life, such as: race, generation, family background, disability and similar. The author expounds the idea of childhood conceived as a social and cultural construct and emphasizes the interpretation of differences between age as biological basis of identity and the fact that identity cannot be drawn from such bases but rather from social and cultural factors. The model for this concept is found in particular in Manheim's concept of generations.